Biochemical and cellular (liver and kidney) restorative properties of garlic (Allium sativum) aqueous extract in cow brain-induced hypercholesterolemic model Swiss albino mice - Kundu, Swarup Kumar; Khan, Mohammad Abu Hadi Noor Ali; Das, Shonkor Kumar (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Garlic is one of the most popular traditional medicinal herbs which has a number of desirable health benefits. The study was designed to depict the improvement of serum biochemical parameters as well as the histomorphological recovery potential of garlic aqueous extract in hypercholesterolemic mice. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A total of thirty Swiss albino mice weighing 24±5g and aged 5 weeks were randomly divided into three groups. Group A: supplied standard mice pellet and water; Group B: standard mice pellet + hypercholesterolemic diet (cow brain: 2 g/kg b.w.t.); and Group C: standard mice pellet + hypercholesterolemic diet (cow brain: 2 g/kg b.w.t.) + garlic extract (25 ml/kg b.w.t.). After four weeks of experimental tenure, samples (blood, liver, and kidney) were collected from each group of mice for serum biochemical analysis and histomorphological study. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Compared with hypercholesterolemic mice, total cholesterol (TC), triglyceride (TG) concentration, and low-density lipoprotein (LDL) levels significantly decreased respectively by 7%, 20% and 48% along with high-density lipoprotein (HDL) levels significantly increased by 47% in garlic extract supplemented group. Based on the histological evaluation in the liver sample of group C, both portal and central veins were normal, and fat droplets were not found in the hepatocytes which were found in the liver of group B. On the other hand, unchanged renal cortex, glomerulus, Bowman’s space, and kidney tubules were seen in group C. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Therefore, the above findings of the present research would assist to provide affirmation about the cholesterol-decreasing and cellular restoration potentiality of garlic aqueous extract.